Management of early PEG tube dislodgement: simultaneous endoscopic closure of gastric wall defect and PEG replacement. Issue 9 (4th September 2019) - Cmorej, Peter; Mayuiers, Matthew; Sugawa, Choichi
Abstract : A 53-year-old man with dysphagia underwent uneventful placement of a percutaneous endoscopic gastrostomy (PEG) tube for long-term enteral feeding access. 11 hours after the procedure, it was discovered that he had accidentally dislodged the feeding tube. On physical examination, he was found to have a benign abdomen without evidence of peritonitis or sepsis. He was observed overnight with serial abdominal examinations and nasogastric decompression. In the morning, he was taken back to the endoscopy suite where endoscopic clips were employed to close the gastric wall defect and a PEG tube was replaced at an adjacent site. The patient was fed 24 hours thereafter and discharged from the hospital 48 hours after the procedure. Early accidental removal of a PEG tube in patients without sepsis or peritonitis can be safely treated with simultaneous endoscopic closure of the gastrotomy and PEG tube replacement, resulting in earlier enteral feeding and shorter hospital stay.